Efficacy of pericapsular nerve group block vs. fascia iliaca compartment block for Hip surgeries: A systematic review and meta-analysis - Ying, Haifeng; Chen, Lingyang; Yin, Danyang; Ye, Yongqing; Chen, Jian (Frontiers in Surgery, 2023)
Objective: The review aimed to compare outcomes of pericapsular nerve group block (PENG) vs fascia iliaca compartment block (FICB) for patients undergoing hip surgeries. Methods: Randomized controlled trials (RCTs) published in the databases of PubMed, CENTRAL, Embase, and Web of Science comparing PENG vs FICB for pain control after hip surgeries were included in the review. Results: Six RCTs were included. 133 patients received PENG block and were compared with 125 patients receiving FICB. Our analysis showed no difference in 6 hour (MD: -0.19 95% CI: -1.18, 0.79 I2=97% p=0.70), 12 hours (MD: 0.04 95% CI: -0.44, 0.52 I2=72% p=0.88) and 24 hours (MD: 0.09 95% CI: -1.03, 1.21 I2=97% p=0.87) pain scores between PENG and FICB groups. Pooled analysis showed that mean opioid consumption in morphine equivalents was significantly less with PENG as compared to FICB (MD: -8.63 95% CI: -14.45, -2.82 I2=84% p=0.004). Meta-analysis of three RCTs showed no variation in the risk of postoperative nausea and vomiting in the two groups. The quality of evidence on GRADE was mostly moderate. Conclusion: Moderate quality of evidence suggests that PENG may result in better analgesia than FICB in patients undergoing hip surgeries. Data on motor-sparing ability and complications are scarce to draw conclusions. Further large-scale and high-quality RCTs should be conducted to supplement current findings.